Souvenir of the Exhibition, 1900 - Au Bon Marché (Paris, France); Exposition universelle, (1900 : Paris, France) ([Paris] : [Impr. Chaix], 1900)
A visitors' guide to the Paris exposition.
"Extract from the Guide and the Agenda-Buvard du Bon Marché."
Includes index.
Mode of access: Internet.
Keywords: Exhibitions; Exhibitions -- France -- Paris; France -- Paris; Paris (France) -- Guidebooks; Guidebooks